Divergent experiences and patterns of integration: contemporary Chinese immigrants in metropolitan Los Angeles, USA. - Zhou, Min; Yang, Ashelee Yue (Journal of Ethnic & Migration Studies, 2022)
Since China's open-door and economic reform in 1979, new waves of emigration from the country have been increasingly diverse with highly skilled immigrants on one hand and unskilled or undocumented immigrants on the other. Based on data from an online survey and in-depth interviews of contemporary Chinese immigrants in metropolitan Los Angeles, we explore two main questions: (1) How do Chinese immigrants negotiate integration and identity as they navigate multiple pathways to resettlement? (2) Why do patterns of convergence and divergence emerge simultaneously and within the same ethnic group? We find that, although Chinese immigrants as a group are economically well-integrated, their lived experiences on the ground do not fit neatly into linear models of assimilation. We also find that their patterns of integration, identity formation, coethnic interaction, and sense of belonging are multivariate, and even peculiar and counterintuitive. These divergent patterns emerge from the interactive processes of immigrant selectivity and social transformations in the context of reception at the dual levels of the host society and ethnic community.